Whole-genome sequencing reveals sex determination and liver high-fat storage mechanisms of yellowstripe goby (Mugilogobius chulae) - Lei Cai (Nature Portfolio, 2021)
Cai and colleagues sequence and annotate the genome of the yellowstripe goby at the chromosome level. Combining genome and transcriptome data, they infer key metabolic pathways for high lipid accumulation in the liver of this fish.